Planning of scenarios for sustainable development in Mexico by 2030 based on expert opinion - Lengyel Almos, Krisztina E (Economía Sociedad y Territorio, 2024)
This article explores the future of sustainable development in Mexico by 2030 through scenario planning. The research is based on expert opinion using qualitative foresight methods. To this end 30 experts were interviewed from the academic, public, and private sectors. Results show a convergence in expert opinion concerning uncertainties that include increased risk in the political environment, deteriorating public safety and disappointing economic growth. Using the cross-matrix methodology, four scenarios were developed that present different potential futures by 2030. The most likely scenario indicates that Mexico is unlikely to meet the Sustainable Development Goals of the UN Agenda 2030.